How mindfulness translates into engagement and flourishing : the role of flow - Tajana Ljubin Golub; Martina Gajšek (International Journal of Emotional Education)
Mindfulness and flow are optimal experiences of consciousness that are positively related to each other and both are associated with enhanced well-being. The current study expanded upon previous work by investigating the hypothesis that flow experienced specifically in academic activities mediates the relationship between dispositional mindfulness and academic engagement and academic flourishing. A sample of 270 university students in Croatia (77% female) completed an online survey that included The Mindful Attention Awareness Scale, The Swedish Flow Proneness Questionnaire for Academic Domain, The Academic Engagement Scale, and The Academic Flourishing Scale. Mindfulness was positively related to academic flow, while both mindfulness and academic flow were associated with higher behavioural and cognitive academic engagement and academic flourishing, and negatively related to anxious engagement. The results of mediation analyses revealed that academic flow is the underlying mechanism for translating the effects of dispositional mindfulness into higher behavioural and cognitive academic engagement, lower anxious engagement and higher academic flourishing. The results are in line with the flow theory and support the role of dispositional mindfulness in engagement in the classroom and flourishing in studying.